2018
DOI: 10.1016/j.celrep.2017.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Induced Mitochondrial ROS Regulate the Early Embryonic Cell Cycle

Abstract: SummaryWhile it is appreciated that reactive oxygen species (ROS) can act as second messengers in both homeostastic and stress response signaling pathways, potential roles for ROS during early vertebrate development have remained largely unexplored. Here, we show that fertilization in Xenopus embryos triggers a rapid increase in ROS levels, which oscillate with each cell division. Furthermore, we show that the fertilization-induced Ca2+ wave is necessary and sufficient to induce ROS production in activated or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 60 publications
(69 reference statements)
5
79
1
Order By: Relevance
“…Using a previously established transgenic line, HyPer (Love et al, 2013;, which allows the assessment of ROS levels in vivo, we recently showed that fertilisation triggers a burst of ROS production in Xenopus, which plays a critical role in the regulation of the early embryonic cell cycle (Han et al, 2017). Here we extend that work by showing that the fertilisation induced rise in ROS levels are sustained throughout early embryonic development.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…Using a previously established transgenic line, HyPer (Love et al, 2013;, which allows the assessment of ROS levels in vivo, we recently showed that fertilisation triggers a burst of ROS production in Xenopus, which plays a critical role in the regulation of the early embryonic cell cycle (Han et al, 2017). Here we extend that work by showing that the fertilisation induced rise in ROS levels are sustained throughout early embryonic development.…”
Section: Introductionsupporting
confidence: 61%
“…Transgenic F1 Xenopus laevis females expressing HyPer maternally were used (Love et al, 2011). Imaging was performed as previously described (Han et al, 2017).…”
Section: Imaging and Detection Of H 2 Omentioning
confidence: 99%
See 2 more Smart Citations
“…These gap junctions could allow for diffusion of small molecules, such as calcium, which could in turn affect the cell cycle. For example, it has been recently suggested that calcium‐induced mitochondrial reactive‐oxygen species could control the cell cycle by regulating Cdc25C activity . Future experiments blocking gap junctions might reveal important insights on the mechanisms of mitotic waves.…”
Section: The Embryonic Cell Cycle: a Bistable Switch Within A Non‐linmentioning
confidence: 99%